’Friends in Pots’ : Growing Bulbs at the Royal Botanic Garden Edinburgh - MacKintosh, Elspeth (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2019)
A method of growing bulbous species with stones as companions to small bulbs is described and illustrated. Statistics for the number of taxa in the ten largest genera in the bulb collection at the Royal Botanic Garden Edinburgh are provided.